Analisis Kausalitas Jumlah Penduduk, Pertumbuhan Ekonomi dan Kesejahteraan Masyarakat di Provinsi Jambi - Dimas Bagus Prayoga; Idris Idris; Ariusni Ariusni (Universitas Negeri Padang, 2019)
This study aims to examine the relation of causality of population, economic growth and prosperity of society in jambi province. The data used is panel data during the period 2004-2016. The data analysis tools used are Panel Granger Causality Test and Panel Vector Autoregression (PVAR). This study finds that the welfare of society does not have causality relation to population, vice versa. People's welfare has a causal relationship to economic growth and vice versa. And the population does not have causality relation to economic growth, but economic growth has relation to population. The results of PVAR found that the welfare of the community during a particular period was significantly influenced by the welfare of the community in the previous period, as well as the population and economic growth.